PENGEMBANGAN GAME EDUKASI PENDIDIKAN AGAMA BUDDHA BERBASIS PROGRESSIVE WEB APPS DENGAN MODEL GAMIFIKASI DAN GDLC - Wahyu, Sawali; Gotama, Jeskel Fornardi (SKANIKA: Sistem Komputer dan Teknik Informatika, 2024)
The use of technology to support people's daily activities has become something normal and usual, positive things that can be accepted and utilized by the community, but negative things must be overcome by applying basic education from an early age, namely to children. Religion is part of the spiritual education implemented in schools, in this case Buddhist Religious Education. The problems and application of these solutions can be presented in the form of non-formal education, namely through Buddhist Sunday School with the implementation of interactive and interesting learning that applies information technology in the form of web-based educational games. The research methodology used is the Game Development Lifecycle (GDLC) which contains a guide to the stages for building a game. The gamification model is used as a learning method by utilizing elements in the game to motivate children to achieve a target achievement. To maximize the performance of the game, Progressive Web Apps is applied to make the application performance better. This research produces a web-based game application that will help Sunday school children access Buddhist Education learning materials by motivating learners. The game was tested using the System Usability Scale method which resulted in a test score of 86 including an A or Excellent rating. As well as the results of UAT (User Acceptance Testing) testing at the beta stage with the results shown with the lowest score being 3 (Agree) and the highest score being 4 (Strongly Agree), thus there is no difficulty in using the educational game because it has clear features and is easy to use.